Sleep Apnea and Total Joint Arthroplasty under Various Types of Anesthesia: A Population-Based Study of Perioperative Outcomes - Memtsoudis, Stavros G. (2013)
BACKGROUND AND OBJECTIVES: The presence of sleep apnea (SA) among surgical patients has been associated with significantly increased risk of perioperative complications. Although regional anesthesia has been suggested as a means to reduce complication rates among SA patients undergoing surgery, no data are available to support this association. We studied the association of the type of anesthesia and perioperative outcomes in patients with SA undergoing joint arthroplasty. METHODS: Drawing on a large administrative database (Premier Inc), we analyzed data from approximately 400 hospitals in the United States. Patients with a diagnosis of SA who underwent primary hip or knee arthroplasty between 2006 and 2010 were identified. Perioperative outcomes were compared between patients receiving general, neuraxial, or combined neuraxial-general anesthesia. RESULTS: We identified 40,316 entries for unique patients with a diagnosis for SA undergoing primary hip or knee arthroplasty. Of those, 30,024 (74%) had anesthesia-type information available. Approximately 11% of cases were performed under neuraxial, 15% under combined neuraxial and general, and 74% under general anesthesia. Patients undergoing their procedure under neuraxial anesthesia had significantly lower rates of major complications than did patients who received combined neuraxial and general or general anesthesia (16.0%, 17.2%, and 18.1%, respectively; P = 0.0177). Adjusted risk of major complications for those undergoing surgery under neuraxial or combined neuraxial-general anesthesia compared with general anesthesia was also lower (odds ratio, 0.83 [95% confidence interval, 0.74–0.93; P = 0.001] vs odds ratio, 0.90 [95% confidence interval, 0.82–0.99; P = 0.03]). CONCLUSIONS: Barring contraindications, neuraxial anesthesia may convey benefits in the perioperative outcome of SA patients undergoing joint arthroplasty. Further research is needed to enhance an understanding of the mechanisms by which neuraxial anesthesia may exert comparatively beneficial effects.